ANALISIS PENGARUH SERVICESCAPE DAN LOKASI TOKO TERHADAP MINAT BELI KONSUMEN (STUDI PADA BUTIK LISDA COLLECTION MALANG, JAWA TIMUR) - Ramanda, Achmad Arizal Ryan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the effect servicescape and store locations on consumer buying interest in Lisda Boutique Collection. Servicescape variables used in this study is the ambient conditions (X1), space and funcionality (X2), and the signs, symbols, and artefacts (X3) as well as other variable is the location of the store (X4). From the results of these studies will be known factor which variables that have a dominant influence on consumer buying interest Lisda Collection boutique. This research uses explanatory research, which is a type of research to explain the relationship between variables servicescape and store locations on consumer buying interest. This study used a sample of 100 respondents drawn from the consumer population Lisda Collection boutique. Sampling using purposive sampling. Test equipment used include validity, reliability and classical assumption. Hypothesis t- test (partial). Data were analyzed using multiple linear regression. Based on the results of the analysis of the t test in can be variable ambient conditions (X1) and variable location of the store (X4) has a significant influence on consumer buying interest in the boutique Lisda Collection, while the variable space and funcionality (X2), and the signs, symbols, and artefacts (X3) had no significant effect on consumer buying interest terhadapa Lisda Collection boutique. The regression analysis based on the most dominant variable is a variable location of the store (X4) by the number of 0.420.Keywords: Servicescape, Store Location, Buying Interest